(untitled) (Theological Kronos, 2018)
The Reverend Martin Luther King Jr., is remembered as one of the most important leaders of the twentieth century of the movement in favor of the civil rights of the black population of the United States. He sought to unite his people in a nonviolent protest against injustice and the defense of the inalienable rights to life, freedom and human dignity. His firm convictions, coupled with his moral integrity and non-violent methods, inspired thousands of Americans to speak out against racial discrimination. Its influence was decisive in abolishing segregation in public places and for the issuance of laws in favor of African-Americans, such as the civil rights law (1964) and the right to vote (1965). This essay commemorates the legacy of Reverend King, systematizing the most relevant aspects of his life and inviting the reader to return to his dream of equality, justice and fraternity.